Search for protein partners of mitochondrial single-stranded DNA-binding protein Rim1p using a yeast two-hybrid system - Kucejová, B; Foury, F (Folia microbiologica, 2003)
RIM1 is a nuclear gene of the yeast Saccharomyces cerevisiae coding for a protein with single-stranded DNA-binding activity that is essential for mitochondrial genome maintenance. No protein partners of Rim1p have been described so far in yeast. To better understand the role of this protein in mitochondrial DNA replication and recombination, a search for protein interactors by the yeast two-hybrid system was performed. This approach led to the identification of several candidates, including a putative transcription factor, Azf1p, and Mph1p, a protein with an RNA helicase domain which is known to influence the mutation rate of nuclear and mitochondrial genomes.
Keywords: DNA vazebné proteiny; Saccharomyces cerevisiae; DNA, Single-Stranded; Fungal Proteins; Two-Hybrid System Techniques; Repressor Proteins; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; jednovláknová DNA; fungální proteiny; transkripční faktory; techniky dvojhybridového systému; DNA, Mitochondrial; represorové proteiny; Transcription Factors; mitochondriální DNA; DNA-Binding Proteins